Translation Analysis of Category Shift in Short Story “The Call of Cthulhu” - Rakhmad Yanuar Hadi Sasmito (English Language Education Study Program of STKIP PGRI Banjarmasin, 2021)
Translation activity have a huge impact on developing knowledge by sharing and implement information from around the world. This study used qualitative method. The research subject is firstly, the short story “The Call of Cthulhu” and the second version which translated into Indonesian “Seruan Cthulhu” by Shinta Dewi from Noura Book Publisher. The aims of this study are to identify what types of category shifts found in the short story and how the information loss, acquisition and skew occur during translation process. In this study, the researcher uses observation technique to collecting the data and documentation to support the data. After conduct the study, the researcher found that the translator used the all type of Category shift when translating the short story: Intra-system shift, Structure shift, Unit shift, and Class shift. From the data collected, it was found that the Intra-system shift was the most dominant shift. This shift occurs because of the need to obtain translation equivalent from both languages. As the result, systematic shifting is unavoidable and has become the most common shift done by translator.